(untitled) (Research, Society and Development, 2022)
This work aims to analyze, through Scientometrics instruments, the main trends related to the production of articles related to aquatic macroinvertebrates in the Amazon biome, mainly with regard to the number of published works, scientific elite, institutions and journals that have published the most. Method: The scientometric study was conducted in the CAPES Journal Portal, with access to the full content, using the Boolean search with the following word combinations: Amazon AND "aquatic macroinvertebrates" OR "aquatic insects" OR "benthic macroinvertebrates" OR "benthic community”. Results: The search resulted in n = 1,003 articles, which, after filtering the selection criteria, n = 73 articles were selected that portrayed the theme related to the study of aquatic macroinvertebrates in the Amazon biome over a 40-year time frame. It was found that the scientific production related to aquatic macroinvertebrates increased from 1981 to 2021. Among the teaching and research institutions that have the largest number of publications in the area are Brazilian and public. Conclusion: Although Brazil has about 60% of the Amazon biome in its territory, occupying 9 of its states, scientific production in the area of ​​aquatic macroinvertebrates in this Biome is still relatively small. Efforts are needed in the training of specialized human resources in the area and incentives to research institutions, thus contributing to the advancement of Science, Technology and Innovation in the Amazon region.